Migratory restlessness and stopover duration in Wood sandpiper Tringa glareola. Issue 3 (4th May 2021) - Vanni, Lorenzo; Cerritelli, Giulia; Turchi, Alessandro; Giunchi, Dimitri
Abstract : Factors affecting stopover duration in birds are still much discussed. Field studies report contradictory evidence regarding the effect of fuel reserves on bird decision to depart from a stopover site, while the majority of laboratory tests performed on passerines reported a positive relationship between body conditions and migratory restlessness. In recent years, a few studies integrating laboratory and field investigations suggested that the amount of migratory restlessness could be a proxy of the individual willingness to depart from a stopover site in night-migrating passerines, but similar studies are lacking for other groups of birds. In this paper the factors affecting stopover length in the Wood sandpiper Tringa glareola (Charadriiformes Scolopacidae) were studied by integrating field observations and laboratory tests during spring migration. Our aims were to investigate (1) the influence of body conditions on migratory restlessness and (2) the influence of body conditions and of the amount of migratory restlessness on stopover duration, after controlling for meteorological conditions. Contrary to our expectations, we did not find any relationship between body condition and migratory restlessness nor stopover duration, while for the 1st time in a non-passerine species, evidence was produced that the amount of migratory restlessness is significantly related to the likelihood of leaving the stopover area. Our results emphasize the relevance of the studies integrating field and laboratory tests to understand the physiological and ecological factors affecting migratory behaviour in different bird species. Highlights: Body conditions seem to be unrelated both to migratory restlessness and stopover duration. Migratory restlessness predicts the likelihood of leaving the stopover site. The quantification of migratory restlessness seems to be a useful tool for studying the effect of intrinsic and extrinsic factors on stopover behaviour in shorebirds.